2022
DOI: 10.1590/1980-5373-mr-2022-0096
|View full text |Cite
|
Sign up to set email alerts
|

Electroless Plating of Ni-P and Ni-P-PTFE on Micro-Arc Oxidation Coatings for Improved Tribological Performance

Abstract: Although micro-arc oxidation (MAO) coatings are widely used for anti-wear protection of metals, they usually contain lots of pores and exhibit high coefficient of friction. In this work, porous MAO coatings consisting of Al 2 TiO 5 were fabricated on the titanium substrate, and then Ni-P and Ni-P-polytetrafluoroethylene (PTFE) were deposited via electroless plating to fill MAO pores and improve the tribological performance. Electroless deposited Ni-P has high wear resistance and the incorporated PTFE particles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Many researchers have successfully prepared Ni-P-nanoPTFE composite coatings on metals and nonmetals and studied the effects of plating solution components, process parameters, dispersion methods, and PTFE content on the wear and corrosion resistance of the coatings [ 19 , 20 , 21 ]. The recent research mainly focuses on the performance of combining Ni-P-nanoPTFE composite coatings with other coatings [ 22 ] or how to increase the PTFE particle content in Ni-P-nanoPTFE composite coatings on substrates in a short time [ 23 ]; however, the research on how to ensure the uniform dispersion of nano-PTFE particles in Ni-P-nanoPTFE composite coatings and reduce the occurrence of missing plating is not perfect. Relevant studies have shown that the combination of an appropriate amount of cationic surfactants and fluorocarbon nonionic surfactants can significantly improve the dispersion of nano-PTFE particles in the solution [ 24 , 25 , 26 ], but this will increase the foaming properties of the plating solution.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have successfully prepared Ni-P-nanoPTFE composite coatings on metals and nonmetals and studied the effects of plating solution components, process parameters, dispersion methods, and PTFE content on the wear and corrosion resistance of the coatings [ 19 , 20 , 21 ]. The recent research mainly focuses on the performance of combining Ni-P-nanoPTFE composite coatings with other coatings [ 22 ] or how to increase the PTFE particle content in Ni-P-nanoPTFE composite coatings on substrates in a short time [ 23 ]; however, the research on how to ensure the uniform dispersion of nano-PTFE particles in Ni-P-nanoPTFE composite coatings and reduce the occurrence of missing plating is not perfect. Relevant studies have shown that the combination of an appropriate amount of cationic surfactants and fluorocarbon nonionic surfactants can significantly improve the dispersion of nano-PTFE particles in the solution [ 24 , 25 , 26 ], but this will increase the foaming properties of the plating solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, ceramic particles were avoided since they may wear the material in contact with rubber, compromising the sealing, and PTFE was chosen among the solid lubricants. PTFE is a low friction and corrosion resistant polymer [14,16,17], known for being self-lubricant [18] and its co-deposition with Ni-P has been shown to significantly decrease the wear rate and CoF of metallic substrates [19][20][21][22][23]. However, as far as the authors are aware, Ni-P-PTFE composite coatings have not been investigated for the protection of non-metallic surfaces, particularly rubber surfaces.…”
Section: Introductionmentioning
confidence: 99%